2001
DOI: 10.1002/yd.23320019006
|View full text |Cite
|
Sign up to set email alerts
|

Community treatment of severely mentally ill offenders under the jurisdiction of the criminal justice system: A review

Abstract: g S . ' ~~k %~ # Community treatment of severely mentally ill offenders who fall under the jurisdiction of the criminal justice system has important dijfferences from treatment ofnonoffenders. It is critical to identijy a treatment philosophy that strikes a balance between individual rights and public safety and includes clear treatment goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 47 publications
0
55
0
Order By: Relevance
“…Since FMHs will have to be shut down and replaced by community facilities (yet to be designed), it is imperative to better study the problem of violence associated to severe mental disorders and to design effective treatment strategies. Indeed living in the community, for the great majority of offenders with serious mental disorders, depends on the availability of appropriately supportive and structured living arrangements (Cohen & Eastman, 1997;Lamb, Weinberger, & Gross, 1999). When patients are not suitable to live with their own family or are unable to live independently (as it is often the case), the availability of RFs can become a critical factor in the provision of support and clinical supervision, and in preventing recidivism in this population.…”
Section: Planning New Services For Violent Patientsmentioning
confidence: 99%
“…Since FMHs will have to be shut down and replaced by community facilities (yet to be designed), it is imperative to better study the problem of violence associated to severe mental disorders and to design effective treatment strategies. Indeed living in the community, for the great majority of offenders with serious mental disorders, depends on the availability of appropriately supportive and structured living arrangements (Cohen & Eastman, 1997;Lamb, Weinberger, & Gross, 1999). When patients are not suitable to live with their own family or are unable to live independently (as it is often the case), the availability of RFs can become a critical factor in the provision of support and clinical supervision, and in preventing recidivism in this population.…”
Section: Planning New Services For Violent Patientsmentioning
confidence: 99%
“…Swartz et al (2001) have suggested that the addition of mandated care to assertive treatment may be necessary to reduce violence. It has been suggested that forensic services may be more effective because they include greater time, thoroughness, legal mandate, or 'whole of life' approach adopted by intensive forensic treatment (Heilbrun and Peters, 2000;Hodgins and Muller-Isberner, 2004;Lamb, Weinberger, & Gross, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Psychiatric disorders, for instance, are documented as being present in 6-19% of incarcerated individuals in the USA, with 23-61% of these individuals receiving some type of psychiatric intervention while under correctional supervision [3,9]. The legal necessity of healthcare provision to individuals with psychiatric disorders is well documented [10], and literature reviews and annual reports give overviews of the mentally ill offender population [3,11,12].…”
Section: Introductionmentioning
confidence: 99%